Financiamento das políticas públicas de trabalho e renda no Brasil: Uma análise a partir da trajetória operacional do Fundo de Amparo ao Trabalhador (FAT) - Sandro Pereira Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– This study analyzes the most relevant political and economic factors that conditioned the institutionalization trajectory of the brazilian Public Employment, Labor and Income System (SPETR). For this, the analytical focus was the financing mechanisms of the Fund of Support to the Worker. Based on a broad analysis of legal instruments and accounting for FAT's annual exercises since its implementation, it has been noted that, as current expenditures have increased in relation to revenues, especially in view of the mandatory constitutional programs (unemployment insurance and salary bonuses), such financing arrangement began to show signs of fragility, since the space to cover discretionary current expenses that make up the other operational dimensions of SPETR has been reduced. However, the main vector of depletion of FAT's financial capacity comes from economic policy decisions within the federal government that have transcended even the decision-making sphere created for this purpose, the Codefat. Decisions with the greatest impact on the system came unilaterally and without any compensation from the economic policy summit of the different governments since the mid-1990s, mainly affecting their revenue stream, particularly revenue earmarking and tax relief.
Keywords: E22; E62; E65; H53; I38; J38; J68; 330; public employment system; Fund of Support to the Worker; social policy; institutional change; job market